Does Hypothermic Circulatory Arrest for Aortic Surgery Trigger Near-Death Experience? Incidence of Near-Death Experiences after Aortic Surgeries Performed under Hypothermic Circulatory Arrest - Mauduit, Marion; Anselmi, Amedeo; Tomasi, Jacques; Belhaj Soulami, Reda; Le Bars, Florent; Flecher, Erwan; Verhoye, Jean-Philippe (AORTA, 2021)
Background Understanding near-death experiences (NDE) could provide a new insight into the analysis of human consciousness and the neurocognitive processes happening upon the approach of death. With a temporary interruption of systemic perfusion, aortic surgery under hypothermic circulatory arrest (HCA) may be the only available model of reversible clinical death. We present, herein, the results of an observational study designed to assess the incidence of NDE after aortic surgery.Methods We performed a prospective study including consecutive patients who underwent thoracic aortic surgery between July 2018 and September 2019 at our institution. Procedures without HCA were included to constitute a control group. The primary outcome was the incidence of NDE assessed with the Greyson NDE scale during the immediate postoperative course, via a standardized interview of the patients in the surgical ward.Results One hundred and one patients were included. Twenty-one patients (20.8%) underwent nonelective interventions for aortic dissection. Ninety-one patients had hemiarch replacement (90.1%). Sixty-seven (66.3%) interventions were performed with HCA, with an average circulatory arrest duration of 26.9 ± 25.5 minutes, and a mean body temperature of 23.7 ± 3.8°C. None of the patients reported any recollection from their period of unconsciousness. There was no NDE experiencer in the study cohort.Conclusion Several confounding factors regarding anesthesia, or NDE evaluation, might have impaired the chance of NDE recollections, and might have contributed to this negative result. Whether HCA may trigger NDE remains unknown.
Keywords: near-death experience; circulatory arrest; hypothermia; aortic surgery